Analisis Determinan Sosial Ekonomi dan Kesejahteraan Petani di Kabupaten Tapanuli Utara - Diwayana Putri Nasution (Universitas Negeri Padang, 2022)
The purpose of this research is to identify and analyze land use change, productivity, education of farmers and family dependents on socio-economic and welfare. The number of samples used was 200 HH data collected by distributing questionnaires and data processing, SEM (Structural Equation Modeling) analysis and Amos software version 23.0. Based on the results of tests carried out by testing the hypothesis on the variables of productivity, farmer education and family dependents, it has a significant effect on farmers' socio-economics. Variables of land conversion, productivity, farmer's education, family dependents and socio-economic have a significant effect on farmers' welfare